Applying Round-Robin Brainstorming on Introduction to Linguistics class - Elfrida BR Silalahi (Universitas Merdeka Malang, 2020)
After knowing the problem faced by the students that they are not familiar with linguistic course whereas it is one of the materials that students must take on college. The purpose of this study to give students solution to learning linguistics. The study concerns with the Introduction to Linguistic course by applying Round-Robin brainstorming technique in class. For this study was conducted Classroom Action Research class as research methodology which was carried out in twocycles in four meetings. Here students on D3 English Program in 4th semester Universitas Merdeka Malang in which consisted of 26 students as a subject. The data quantitative was collected by giving essay test. By using Round-Robin Brainstorming technique students' scores kept improved in every test. The finding is the mean of the Round–Robin Brainstorming technique on second cycle (80. 55) Was higher than the first cycle (74.95) and orientation test (69.65). This research proved that applying the Round–Robin Brainstorming technique was significantly enhanced on students’comprehension in Linguistic course. Keywords: Round-Robin brainstorming, teaching technique, linguistics, classroom action research DOI: 10.26905/enjourme.v5i2.4048